The immune system response to the SARS-CoV-2 virus: July 2020 update - Klenerman, Paul (Henry Stewart Talks, 2020)
Current knowledge of the immune response to SARS-CoV-2, Involvement of the T cell response, Testing and detecting the antibody and T cell response, Hypotheses on the range of responses to the virus, Future steps